Taxation of capital gains and lock-in effect in the Spanish Dual Income Tax - Carlos Díaz Caro; Eva Crespo Cebada (European Journal of Management and Business Economics (EJM&BE), 2016)
The aim of this paper is to study the possible change in the individual behaviour of the Spanish taxpayers about the willingness to declare capital gains, Lock-in effect, as a consequence of variations in the marginal rate. To do this, a two stages model is proposed to analyze which variables affect both the probability, and the amount, of capital gains declarations. The empirical analysis was performed using the Spanish annual personal income tax return sample from IEF-AEAT (Institute of Fiscal Studies and the Tax Department) for the periods 2006 and 2007, corresponding to the years before and after the reform that introduced a Dual Income Tax in Spain, with a flat tax rate for capital gains tax. The main results show that a 1% increase in the capital gains tax rate reduces the probability of declaring capital gains by around 7.51% (2006) and 8.19% (2007), and the amount of capital gains by around 3.91% (2006) and 5.79% (2007).
Keywords: D31; H23; H24; 650; Capital gains; Dual Income Tax; Lock-in; Taxation